2020
DOI: 10.1111/bju.15173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐energy shock wave therapy on intravesical epirubicin delivery in a rat model of bladder cancer

Abstract: To study the efficacy of low-energy shock wave therapy (LESW) on enhancing intravesical epirubicin (EPI) delivery in a rat model of bladder cancer (BCa). Materials and Methods A total of 100 female Fischer rats were randomly allocated into five groups: control; BCa; LESW; EPI; and EPI plus LESW. After BCa induction by N-butyl-N-(4-hydroxybutyl)nitrosamine, EPI (0.6 mg/0.3 mL of EPI diluted in 0.3 mL saline) or saline (0.6 mL) was administered and retained in the bladders for 1 h with or without LESW treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The combination of intravesical epirubicin and LESW results in reduced cancer cell invasion and urothelial cell dysplasia. In that study, LESW was shown to increase urothelial permeability and enhance the delivery of the drug into tumor tissues without subsequent toxicity [ 86 ].…”
Section: Lesw Ameliorates Bladder Inflammation and Might Promote Urot...mentioning
confidence: 99%
“…The combination of intravesical epirubicin and LESW results in reduced cancer cell invasion and urothelial cell dysplasia. In that study, LESW was shown to increase urothelial permeability and enhance the delivery of the drug into tumor tissues without subsequent toxicity [ 86 ].…”
Section: Lesw Ameliorates Bladder Inflammation and Might Promote Urot...mentioning
confidence: 99%
“…Some studies have focused on improving the focal permeability of macromolecular cytotoxic drugs into specific cancer tissue [ 32 ]. For example, some studies have reported that LESW combined with chemotherapy can improve the treatment efficacy of chemotherapy by increasing the intracellular drug concentration [ 28 , 33 ]. In this study, we observed a similar result in vitro and in vivo and further identified decreased expression of the tight junction protein ZO-1 and the adherent junction protein E-cadherin when chemotherapy was used in combination with LESW.…”
Section: Discussionmentioning
confidence: 99%
“…SWs introduce a great positive pressure, further increase the mammalian cell membrane permeability, and transiently induce membrane pore formation, thus allowing macromolecular drugs to enter cells and elicit their therapeutic effects 5 . Currently, SWs are known to enhance the cytotoxicity of chemotherapeutic drugs in several types of carcinoma, including breast 6 , bladder 7 , and prostate cancers 8 , although SWs alone show little inhibitory influence on tumour growth. In a Mat B-III syngeneic rat breast cancer model, SWs and the chemical protoporphyrin IX have been demonstrated to decrease the tumour size with stronger necrotic and apoptotic clinical histological features compared to protoporphyrin IX alone 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In a Mat B-III syngeneic rat breast cancer model, SWs and the chemical protoporphyrin IX have been demonstrated to decrease the tumour size with stronger necrotic and apoptotic clinical histological features compared to protoporphyrin IX alone 6 . In addition, low-energy SWs have been shown to promote intravesical epirubicin delivery in bladder cancer, followed by reduced metastasis and dysplasia formation 7 . Moreover, SW treatment has been reported to inhibit the activation of cancer-associated fibroblasts as well as to decrease androgen-resistant prostate cancer cell growth and invasion 8 .…”
Section: Introductionmentioning
confidence: 99%